2012
DOI: 10.1174/021347412800337933
|View full text |Cite
|
Sign up to set email alerts
|

Menores con conducta de maltrato hacia los progenitores: un estudio de personalidad y estilos de socialización

Abstract: El propósito de esta investigación es determinar si existen características de personalidad y estilos de socialización parental diferenciales entre los adolescentes que agreden a sus progenitores y aquellos que no lo) hacen. Para ello se aplicó el MACI (Inventario Clínico para Adolescentes de Millon) y el ESPA29 (Escala de Socialización Parental en la Adolescencia de Musitu y García) en una muestra de 14 adolescentes (9 varones y 5 mujeres), con edades comprendidas entre los 14 y 18 años e internados en Centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
0
22
0
8
Order By: Relevance
“…Some studies have analyzed specific risk factors of CPV (Beckmann et al, in press;Ibabe, Jaureguizar, & Bentler, 2013;Pagani et al, 2004Pagani et al, , 2009, and certain factors have been found repeatedly among offenders and their families. Perpetrators often face mental health issues, such as depression, ADHD or antisocial personality disorders (Castañeda, Garrido-Fernández, & Lanzarote, 2012;Coogan, 2014;Ibabe & Jaureguizar, 2010;Routt & Anderson, 2011). Compared to young offenders who had committed crimes other than CPV, CPV offenders were found to have worse psychopathological profiles, with 30% having received a clinical diagnosis (most commonly ADHD), while no clinical diagnoses were found in the non CPV sample (Contreras & Cano, 2015).…”
Section: Research On Cpv: What Do We Know?mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have analyzed specific risk factors of CPV (Beckmann et al, in press;Ibabe, Jaureguizar, & Bentler, 2013;Pagani et al, 2004Pagani et al, , 2009, and certain factors have been found repeatedly among offenders and their families. Perpetrators often face mental health issues, such as depression, ADHD or antisocial personality disorders (Castañeda, Garrido-Fernández, & Lanzarote, 2012;Coogan, 2014;Ibabe & Jaureguizar, 2010;Routt & Anderson, 2011). Compared to young offenders who had committed crimes other than CPV, CPV offenders were found to have worse psychopathological profiles, with 30% having received a clinical diagnosis (most commonly ADHD), while no clinical diagnoses were found in the non CPV sample (Contreras & Cano, 2015).…”
Section: Research On Cpv: What Do We Know?mentioning
confidence: 99%
“…Other individual factors related to the perpetrator such as lower self-esteem (Calvete et al, 2011;Ibabe et al, 2014a;Ibabe, Arnoso, & Elgorriaga, 2014b;Pereira & Bertino, 2010), lower empathy (Castañeda et al, 2012;Ibabe & Jaureguizar, 2010), higher impulsivity (Calvete et al, 2011;Ibabe et al, 2014a;Pereira & Bertino, 2010), and lower frustration tolerance (Kennair & Mellor, 2007;Nock & Kazdin, 2002) have been linked to CPV offenders, both compared to youth of normal profiles as well as young offenders. Tied in with mental health and individual profile characteristics are issues of substance abuse (Calvete et al, 2011;Castañeda et al, 2012;Ibabe et al, 2013;Routt & Anderson, 2011), which are found at even higher rates in CPV cases compared to other young offenders (Ibabe & Jaureguizar, 2010;Ibabe, Jaureguizar, & Díaz, 2009).…”
Section: Research On Cpv: What Do We Know?mentioning
confidence: 99%
See 1 more Smart Citation
“…Asimismo, en futuras investigaciones sería interesante observar las diferencias entre chicos y chicas, ya que los estudios previos sobre violencia filio-parental y violencia hacia los iguales muestran resultados contradictorios sobre esta cuestión. Así, mientras en algunos estudios no se observan diferencias entre chicos y chicas (Card et al, 2008), en otros trabajos se indica una mayor utilización de las conductas violentas, tanto hacia los iguales como hacia los progenitores, por parte de los chicos (Díaz-Aguado et al, 2010;Routt y Anderson, 2011). Además, en la realización de estos estudios se tiene que diferenciar entre los diferentes tipos de violencia, manifiesta y relacional, pura, reactiva e instrumental; y tener en cuenta el tipo de muestra, si es clínica, judicial o comunitaria, ya que los resultados pueden diferir considerablemente dependiendo de estos factores (Bobic, 2002;Card, et al, 2008;Routt y Anderson, 2011).…”
Section: Conclusionesunclassified
“…Un clima familiar positivo puede prevenir la aparición de conductas desajustadas en los adolescentes (Megías, Elzo, Megías, Méndez, Navarro y Rodríguez, 2002) y, a su vez, amortiguar el malestar psicológico que sufren algunos adolescentes que son víctimas de violencia escolar (Povedano, Hendry, Ramos y Varela, 2011). Por el contrario, si los menores presencian conflictos de los padres envueltos de violencia verbal y física suponen un alto factor de riesgo que los predispone a la conducta violenta (Castañeda, Garrido-Fernández y Lanzarote, 2012). La observación de la violencia en el contexto familiar favorece que los niños y niñas aprendan a ejercer la violencia contra otras personas (Gámez-Guadix y Calvete, 2011).…”
Section: Introductionunclassified